Influence of fruit juice consumption before two years of age on the development of childhood obesity (Research, Society and Development, 2023)
Objectives: to describe the main data published in the literature, between the years 1990 and 2023, to better understand the influence of the consumption of fruit juices under two years of age on the development of childhood obesity. Methodology: the present study is a literature review where 55 articles on the subject were selected from the MEDLINE and Scielo databases from august 2020 to july 2023 and critically analyzed according to the relationship between the consumption of fruit juices in children under two years of age and obesity in adults. Result: studies have shown that the grinding step of the fruit for juice production removes fibers from its composition, negatively affecting gastrointestinal dynamics. In addition, fructose (i.e., found primarily in fruits) has a complex metabolism and accumulates adipose tissue if no associated fiber is consumed. It is also suggested that the balanced intake of juices throughout the first years of life prevents the accumulation of body fat in childhood and youth. Conclusion: excessive consumption of fruit juices should be avoided under two years of age, since their intake can contribute to the development of obesity and lead to important consequences from childhood to adulthood.